Pengaruh Pemberian Air Rebusan Daun Pandan Wangi dan Jahe Terhadap Penurunan Tekanan Darah Penderita Hipertensi di Desa Butungale Kecamatan Popayato Barat - Lahiya, Ummunnisa; Febriyona, Rona; Sudirman, Andi Nur Aina (Jurnal Keperawatan Muhammadiyah, 2024)
Objective: The impacts that can arise from hypertension include complications. Therefore treatment is needed for hypertension. Herbal plants that have potential as traditional medicinal plants that can reduce hypertension are fragrant pandan leaves combined with ginger. Forconducted an analysis of the effect of giving a decoction of fragrant pandan leaves and ginger on reducing blood pressure in elderly people with hypertension in Butungale Village, West Popayato District, Pohuwato Regency. Methods: Usepre-experimentdesign, with a one group pre test – post test design. Results: Research found thatBased on the results of statistical tests using the Paired t test, it is known that the p value = 0.000<0.05, then Ha is accepted, so it can be concluded that there is an effect of giving a decoction of fragrant pandan leaves and ginger on reducing the blood pressure of hypertension sufferers in the West Poapayato Health Center Working Area Butungale Village, Pohuwato Regency. Conclusion: Elderly people with hypertension can use boiled water from fragrant pandan leaves combined with ginger for therapy so that they do not develop severe hypertension because hypertension is a disease that will not be easily cured just by using medicine but requires other therapy such as herbal therapy using fragrant pandan leaves and ginger.